Design thinking model integrating Naik Dango local wisdom to foster junior high students’ 4C skills - Handi Darmawan; Pitalis Mawardi; Basuki Wibowo; Eka Trisianawati; Nurbani Nurbani (University of Muhammadiyah Malang, 2026)
Background: In biology learning, integrating the local wisdom with design thinking offers a contextual and innovative approach to empowering students’ 4C skills. However, previous studies have rarely integrated local wisdom as a pedagogical mechanism within the design thinking framework. Methods: This study employed a Research and Development approach based on the Plomp model, consisting of three stages: preliminary research, prototyping, and assessment. Participants were 85 junior high school students in Ngabang City, West Kalimantan, divided into an experimental group and a control group. Data were collected through validation, observation, and questionnaires, and analyzed using ANCOVA to assess the model’s validity, practicality, and effectiveness. Results: The results of the validity test showed that all learning materials were valid, with reliability ranging from substantial to perfect. The practicality evaluation indicated that the Naik Dango learning model integrated with design thinking was very well received by students, with an average positive response rate of 87.20%. The effectiveness test revealed a significant improvement in students’ 4C skills, as indicated by p-values of less than 0.05 for each skill dimension. Conclusion: The Naik Dango learning model integrated with design thinking was valid, practical, and effective in enhancing students’ 4C skills.